FePO4 based single chamber air-cathode microbial fuel cell for online monitoring levofloxacin - Zeng, L.; Li, X.; Shi, Y.; Qi, Y.; Huang, D.; Tadé, M.; Wang, S.; Liu, Shaomin (Elsevier BV, 2017)
A bio-electrochemical strategy was developed for constructing a simple and sensitive levofloxacin (LEV) sensor based on a single chamber microbial fuel cell (SC-MFC) using FePO4 nanoparticles (NPs) as the cathode catalyst instead of traditional Pt/C. In this assembled sensor device, FePO4 NPs dramatically promoted the electrooxidation of oxygen on the cathode, which helps to accelerate the voltage output from SC-MFC and can provide a powerful guarantee for LEV detection. Scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS) were used to fully characterize the FePO4 NPs. Under the optimized COD condition (3 mM), the LEV with a concentration range of 0.1–1000 µg/L could be detected successfully, and exhibited the excellent linear interval in the concentration range of 0.1–100 µg/L. During this range of concentrations of LEV, a temporary effect on the anode of exoelectrogenic bacterial in less than 10 min could occur, and then came back to the normal. It exhibited a long-term stability, maintaining the stable electricity production for 14 months of continuous running. Besides, the detection mechanism was investigated by quantum chemical calculation using density functional theory (DFT).